Meta-Analysis of Inquiry Learning Models in Physics Learning - Sharvina Yudatika; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Universitas Lambung Mangkurat, 2021)
This study aims to analyze the effect of inquiry in physics learning which can be viewed in terms of education, results, materials, and research on the learning media used. The method used is Meta-Analysis with the research flow, namely determining the research topic, setting data criteria, searching for data, classifying data, analyzing and drawing conclusions. Data collection techniques using secondary data from 23 relevant articles from previous scientific publications. The data analysis technique uses effect size. The results of this meta-analysis conclude that the application of the inquiry learning model has a significant effect on physics learning, with an effect size value of 1.216. The application of inquiry in physics learning has a considerable impact if applied to the elementary school education level by producing outputs that increase understanding of concepts, use light subjects, and help learning media in worksheets.